Washback in Language Testing: A Literature Review of Positive and Negative Influences on Teaching and Learning - Merry Christiana (STKIP Taman Siswa Bima, 2025)
Washback, the influence of testing on teaching and learning, is a critical issue in language education with the potential to produce both beneficial and harmful effects. This literature review aims to provide an updated understanding of this phenomenon by synthesizing empirical and theoretical research published between 2018 and 2025. Employing a qualitative document analysis of 12 peer-reviewed articles, this study interprets recent findings through the theoretical lenses of Bachman and Palmer’s (1996) model of test usefulness and Carr’s (2011) framework of tests as decision-making tools. The review identifies three primary conclusions: (1) assessment design is a key determinant of washback, with product-oriented tests frequently leading to negative outcomes while process-oriented and formative tests foster positive ones; (2) washback is deeply embedded in its context, with socio-political and economic factors often overriding the test's intended effects; and (3) stakeholders, particularly teachers, are the ultimate mediators of washback, with their assessment literacy and beliefs playing a crucial role. The study concludes that washback is a complex ecosystem resulting from the interplay between the test, the context, and the people involved. Creating positive washback requires a holistic approach that improves not only test design but also invests in teacher training and mitigates negative contextual pressures.